Digitale Medien in Betrieben - heute und morgen : eine Folgeuntersuchung - Gensicke, Miriam [Verfasser]; Bechmann, Sebastian [Verfasser]; Kohl, Matthias [Verfasser]; Schley, Thomas [Verfasser]; Garcia-Wülfing, Isabel [Verfasser]; Härtel, Michael [Verfasser] (Bundesinstitut für Berufsbildung, 2020)
"Der digitale Transformationsprozess in der Arbeits- und Berufswelt ist in vollem Gange und wirkt sich ebenso auf die Berufsbildung aus. Wie schnell verändert sich der Einsatz digitaler Medien im Betriebsalltag sowie in der Aus- und Weiterbildung in den einzelnen Branchen und unterschiedlichen Betriebsgrößen, wo liegen die Herausforderungen und welchen Handlungs- und Modernisierungsbedarf gibt es vier Jahre nach der ersten Untersuchung? Die zweite repräsentative Betriebsbefragung gibt Aufschluss über die derzeitige Nutzung und Einbindung digitaler Medien in den betrieblichen Arbeitsprozessen sowie in der beruflichen Aus- und Weiterbildung. Ergänzt wird die Studie durch eine qualitative Befragung, in der analysiert wird, welche Maßnahmen Betriebe in der technologischen Infrastruktur und in der Organisationsentwicklung ergriffen haben oder derzeit umsetzen. Die Studie wurde vom Bundesinstitut für Berufsbildung im Auftrag des Bundesministeriums für Bildung und Forschung zusammen mit Kantar und dem Forschungsinstitut Betriebliche Bildung durchgeführt." (Hrsg., BIBB-Doku)

"The digital transformation process in the world of work and employment is already well underway and is likewise impacting vocational education and training. How rapidly is use of digital media changing in everyday working life, in initial and continuing vocational education and training, within the individual sectors, and across different company sizes? What challenges must be met and what are the action and modernisation requirements four years after the initial study? This second representative company survey provides insight into the current implementation and integration of digital media in company-based work processes and in initial and continuing vocational education and training. The study is backed up by a qualitative survey, which analyses which measures companies have initiated or are currently implementing in their respective technological infrastructure and in their organisational development. Which specific requirements exist regarding staff training so as to facilitate shaping the digital shift? Which barriers persist in the digitalisation process? What type of support needs to be provided to company-based training staff to enable them to establish a digital culture of learning/teaching? The present publication provides answers to these and many other questions. The study was carried out by the Federal Institute for Vocational Education and Training (BIBB) on behalf of the Federal Ministry of Education and Research and was conducted in conjunction with Kantar and the Research Institute for Vocational Education and Training (f-bb)." (Editor, BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; G 2.2.1 Technologisierung; L 4.1.2 Elektronische Medien; T 3.4 Befragung; L 3 Lehr-Lern-Forschung; Betrieb; Digitalisierung; Digitale Medien; Mediennutzung; Medieneinsatz; Arbeitsprozess; Betriebliche Berufsausbildung; Berufliche Weiterbildung; Weiterbildungsbedarf; Betriebsbefragung; Learning Analytics